Treatment of Psychosis in College Counseling Centers: Therapist Experiences and Recommendations. Issue 2 (2nd April 2020) - Fruchter, Marissa G.; Brabender, Virginia M.
ABSTRACT: This qualitative study examined the treatment of psychosis in college counseling centers. The goals were to find out how student-patients present, how therapists approached treatment with students with psychosis, how treatment proceeded, and what recommendations therapists had for improving treatment of this population. The investigator interviewed 10 therapists who have worked in college counseling centers and have treated at least one student with psychosis in this setting. Four major interview themes emerged: system factors, treatment demands, student-patient profiles, and recommendations. It was found that the treatment taking place in counseling centers is generally consistent with what has been suggested in the literature for other settings. However, in some ways the practical, concrete focus of treatments sometimes resulted in certain aspects of treatment being overlooked, such as helping students make meaning of their experiences in the larger context of their lives. Suggestions for treatment and future directions were discussed.